The Essence Of Leadership In The Tafsir Of Sayyid Qutb - Ahmad Zabidi; Sri Sunantri; Maulana (Jurnal Ilmu Sosial dan Humaniora, 2024)
The essence of leadership is important to understand and actualize in community life, this is due to seeing various phenomena that occur in society in everyday life which always clash with applicable rules or norms and laws. So an attitude of tolerance is needed in dealing with problems that occur in society. The aim of the research is to describe the essence of leadership in Sayyid Qutb interpretation, the research method uses library research (literature study) through content analysis. The research results show that the Caliph has the position of leader and enforcer of Allah's laws on earth. A caliph is a person who exercises power and management of a particular area in a community. A caliph, apart from being a political leader, can also refer to humans in general who are indicated as God's representatives on earth in carrying out their mandate well, being used as leaders as priests to be emulated, and ulil amri to be obeyed in terms of goodness, carrying out good deeds and enforcing justice. amidst society.